2021
DOI: 10.1155/2021/8886699
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Inflammatory Effect of Zhibaidihuang Decoction on Recurrent Oral Ulcer with Sirt1 as the Key Regulatory Target

Abstract: The syndrome of ROU is generally manifested as obvious pain, redness, and swelling of local ulceration area, accompanied by flushed face, red eyes, sore throat, and swollen gums. Traditional Chinese medicine (TCM) doctors believe that “yin deficiency” is one causative factor of ROU. Zhibaidihuang decoction (ZBDHD) is a prescriptively developed receipt, where Anemarrhena asphodeloides and Phellodendri amurensis Cortex are added in the original Liuweidihuang decoction. It is generally used for “yin deficiency” t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Furthermore, it can control fasting and postprandial blood glucose and bring them to a desirable level ( Cao et al, 2010 ; Lian et al, 2015 ; Huang et al, 2019 ). However, due to the complex composition of herbs, the unclear mechanism of TCM formulas ( Shao et al, 2021 ; Yuan et al, 2021 ; Yun et al, 2021 ), and a lack of scientific data to support the dose-response relationship ( Huang et al, 2017 ; Ge et al, 2018 ), the clinical dosage modification usually lacks standardization and has become a bottleneck for detailed studies on TCM.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it can control fasting and postprandial blood glucose and bring them to a desirable level ( Cao et al, 2010 ; Lian et al, 2015 ; Huang et al, 2019 ). However, due to the complex composition of herbs, the unclear mechanism of TCM formulas ( Shao et al, 2021 ; Yuan et al, 2021 ; Yun et al, 2021 ), and a lack of scientific data to support the dose-response relationship ( Huang et al, 2017 ; Ge et al, 2018 ), the clinical dosage modification usually lacks standardization and has become a bottleneck for detailed studies on TCM.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ZBDHP may improve fatty acid metabolism and treat RAS by regulating the Sirt1-NF-κB pathway. [ 16 ] A large number of systematic reviews and meta-analyses have been conducted to estimate the efficacy of TCM in the treatment of RAS. For example, Zhou et al [ 17 ] systematically reviewed the efficacy and safety of Chinese medicines in treating RAS.…”
Section: Introductionmentioning
confidence: 99%
“…12 Shao et al found berberine, as well as other compounds, could increase the expression of Sirt1 and Foxp3 and suppress the expression and acetylation of NF-κB in oral mucosa cells. 13 A randomized controlled trail found that HB has better effects than bingpeng powder in the ulcer healing in patients with RAS. 14 Although several studies have reported on the anti-RAS activity of HB, the mechanisms of HB contributing to therapeutic effects remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…14 Although several studies have reported on the anti-RAS activity of HB, the mechanisms of HB contributing to therapeutic effects remain unclear. 13 , 15 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation